Lipase catalyzed betulinic acid derivatives and its cytotoxic activity / Yamin Yasin and Faujan Ahmad - Ahmad, Faujan (Research Management Institute (RMI), 2010)
Betulinic acid, a triterpenoid found in many plant species, has attracted attention due to its important pharmacological properties, such as anti-cancer and anti-HIV activities. In order to obtain derivatives potentially useful for detailed pharmacological studies, derivatives were synthesized through the reaction of betulinic acid with benzoyl chloride and acetic anhydride using a lipase catalyst. Enzyme-catalyzed reaction of betulinic acid with benzoyl chloride yielded 3B-benzoil-lup-20(29)-ene-28-oic acid ester (BCL), whereas the acetic anhydride reaction yielded 3B-acetoxy-lup-20(29)-ene-28-oic acid ester (BAA). The BAA underwent further reaction with l-decanol to produce 3B-acetoxy-lup-20(29)-ene-28 decanoate (BAAD). The prepared betulinic acid derivatives were tested for cytotoxic activity on three callcer cell lines in vitro: all tested compunds showed greater activity than betulinic acid.